Modulation of cell proliferation, survival and gene expression by RAGE and TLR signaling in cells of the innate and adaptive immune response: role of p38 MAPK and NF-KB - Medeiros, Marcell Costa de [UNESP]; Tfaile Frasnelli, Sabrina Cruz [UNESP]; Bastos, Alliny de Souza [UNESP]; Orrico, Silvana Regina Perez [UNESP]; Rossa Júnior, Carlos [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2014)
Objective: The aim of this study was to evaluate a possible synergism between AGE-RAGE and TLR4 signaling and the role of p38 MAPK and NF-kB signaling pathways on the modulation of the expression of inflammatory cytokines and proliferation of cells from the innate and adaptive immune response. Material and Methods: T lymphocyte (JM) and monocyte (U937) cell lines were stimulated with LPS and AGE-BSA independently and associated, both in the presence and absence of p38 MAPK and NF-kB inhibitors. Proliferation was assessed by direct counting and viability was assessed by a biochemical assay of mitochondrial function. Cytokine gene expression for RAGE, CCL3, CCR5, IL-6 and TNF-alpha was studied by RT-PCR and RT-qPCR. Results: RAGE mRNA expression was detected in both cell lines. LPS and AGE-BSA did not influence cell proliferation and viability of either cell line up to 72 hours. LPS and LPS associated with AGE induced expression of IL-6 and TNF-alpha in monocytes and T cells, respectively. Conclusions: There is no synergistic effect between RAGE and TLR signaling on the expression of IL-6, TNF-alpha, RAGE, CCR5 and CCL3 by monocytes and lymphocytes. Activation of RAGE associated or not with TLR signaling also had no effect on cell proliferation and survival of these cell types.
Keywords: Periodontal diseases; Diabetes mellitus; Innate immunity; Acquired immunity; Advanced glycosylation end products